2015
DOI: 10.1534/g3.115.017376
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic Mutational Analysis of a Histone H3 Residue in Budding Yeast Provides Insights into Chromatin Dynamics

Abstract: In previous work using the Saccharomyces cerevisiae model system, a mutant version of histone H3—H3-L61W—was found to confer a variety of abnormal growth phenotypes and defects in specific aspects of the transcription process, including a pronounced alteration in the distribution pattern of the transcription elongation factor Spt16 across transcribed genes and promotion of cryptic transcription initiation within the FLO8 gene. To gain insights into the contribution of the H3-L61 residue to chromatin function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Mutations in SPT16 made the promoter of SER3 accessible for transcriptional factors and therefore derepressed the SER3 gene [78]. Multiple subsequent studies have reported loss of nucleosomes from transcribed genes in a transcription-dependent manner following yFACT depletion, which was accompanied by the appearance of short transcripts that originated from cryptic TSSs within the coding regions of yeast genes [66,[78][79][80][81][82][83][84][85]. FACT was also shown to be a critical factor in the repression of cryptic initiation of intragenic promoters genome-wide in plants [86].These data cumulatively suggest that in vivo, yFACT is clearly important for preserving chromatin structure at transcribed genes.…”
Section: Fact In Transcriptionmentioning
confidence: 99%
“…Mutations in SPT16 made the promoter of SER3 accessible for transcriptional factors and therefore derepressed the SER3 gene [78]. Multiple subsequent studies have reported loss of nucleosomes from transcribed genes in a transcription-dependent manner following yFACT depletion, which was accompanied by the appearance of short transcripts that originated from cryptic TSSs within the coding regions of yeast genes [66,[78][79][80][81][82][83][84][85]. FACT was also shown to be a critical factor in the repression of cryptic initiation of intragenic promoters genome-wide in plants [86].These data cumulatively suggest that in vivo, yFACT is clearly important for preserving chromatin structure at transcribed genes.…”
Section: Fact In Transcriptionmentioning
confidence: 99%
“…We have recently used a version of this histone mutagenesis strategy to generate histone H3 proteins expressing all possible amino acid substitutions at position 61, which is normally occupied by the amino acid leucine 14 . For those experiments, instead of using yAAD156 as the starting strain for the mutagenesis, we used strain yADP106, which harbors a replacement of the HHT2 ORF with both the URA3 and TRP1 nutritional markers (instead of just URA3).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since the AG to GA mutation generates a new EcoRI restriction site, we subjected PCR products from one of the successful integration samples to an EcoRI digestion and were able to demonstrate that the mutant sequence had indeed been integrated into the genome (see Figure 4B). In this particular case we did not sequence the PCR products to ensure that additional unwanted mutations had not been incorporated into the genome: however, we have used a procedure very similar to this to generate a large number of HHT2 mutations in a past study 14 , and found that the majority of the integrated mutant alleles carry no mutations other than the desired ones. with cells subjected to the co-transformation procedure after a 3-day incubation at 30˚C.…”
mentioning
confidence: 99%
“…To identify additional factors that promote Spt16 dissociation from genes, we carried out a synthetic gene array (SGA) screen to probe for genetic interactions between an ISGI mutant and deletions in each of~4800 genes available in a yeast haploid non-essential gene deletion library [46]. For this screen we used the H3-L61T ISGI mutant as the query strainthe H3-L61T mutant causes a strong defect in Spt16 dissociation from the 3′ ends of genes but does not confer a growth defect at 30°C and only moderate growth defects at 14°C and 37°C ( [48] and Figure 1a). We reasoned that the combined effects of H3-L61T and deletion of a gene encoding a protein involved in Spt16 gene dissociation would lead to a defect in Spt16 gene dissociation severe enough to result in a synthetic sick or lethal phenotype.…”
Section: A Genetic Screen Uncovers a Potential Connection Between Rttmentioning
confidence: 99%
“…Following mating between the query and the deletion strains and sporulation of the resulting diploids, double mutant meiotic products were screened for synthetic growth defects at 30°C and 14°C (see Materials and methods). The latter temperature was chosen because in previous studies we found that the three ISGI mutants that cause the most severe Spt16 gene dissociation defects -H3-L61K, H3-L61W, and H4-R36Aalso confer strong growth defects at 14°C (Cs − phenotype [41,48,49]), thus pointing to a possible correlation between strong Spt16 gene dissociation defects and cold sensitivity.…”
Section: A Genetic Screen Uncovers a Potential Connection Between Rttmentioning
confidence: 99%